Cidade quebrada: terra dividida, espaço comum - Mendes, Lucas Eduardo Tozzi [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work is the elaboration of a reporting-book that treats the city of Bauru not just as a geographic place and background for events, but as a social space, where material and symbolic human achievements take place with relations of Power in society. In order to specify the proposal, three themes were chosen to be analyzed: social and income inequality; Urbanization / right to housing and resistance organized by groups or people in the city. There are two hypotheses for reporting-book: the city of Bauru applies and reiterates in the same proportions the reproduction logic of brazilian social inequality, as pointed out in a study by Jesse Souza (IPEA) and Housing Policy applied in the city follows the undemocratic model of real estate speculation and housing financialization. The reporting-book is inserted in a context of deep inequalities in Bauru, the 21st largest economy on State of São Paulo, while more than 100.000 people, almost ⅓ of population, are in Low-income situation. The issue of housing is impacted for accelerated brazilian urbanization, and the problems arising from real estate speculation, such as gentrification, urban voids and peripheralization are present in Bauru. In response to this scenario, militants, groups and organizations articulate in city as a way to resist, occupy and claim their rights. The reporting used journalistic techniques of documentation, style, narrative structure, coding system, layout and editing. In gist, to question and affirm the role of the Communicator in society, as a category that carries a social function and of relevant and crucial importance for denunciation and social criticism, for the formation of political consciousness and the construction of the public sphere

O trabalho proposto é a elaboração de um livro-reportagem que trata da cidade de Bauru não apenas como lugar geográfico e pano de fundo para os acontecimentos, mas enquanto espaço social, onde acontecem as realizações humanas materiais e simbólicas e onde se reproduzem as relações de poder da sociedade. Para especificar a proposta foram escolhidos três temas para serem destrinchados no livro: desigualdade social e de renda; urbanização/direito à moradia e a resistência organizada por grupos ou pessoas na cidade. Existem duas hipóteses para a reportagem, baseadas nos estudos que motivaram sua execução: a cidade de Bauru aplica e reitera nas mesmas proporções a lógica de reprodução da desigualdade social existente a nível nacional, como apontado em estudo de Jessé Souza (IPEA) e a Política Habitacional aplicada no município segue o modelo antidemocrático da especulação imobiliária e financeirização da moradia. O livro-reportagem se insere num contexto de profundas desigualdades em Bauru, cidade na qual encontra-se o 21º maior PIB do Estado de São Paulo ao mesmo tempo em que mais de 100 mil pessoas, quase um terço da população, encontram-se em situação de baixa renda. A questão da moradia recebe os impactos da acelerada urbanização brasileira, e os problemas decorrentes da especulação imobiliária, como gentrificação, vazios urbanos e periferização se fazem presentes em Bauru. Em resposta à esse cenário, militantes, grupos e organizações se articulam na cidade como forma de resistir, ocupar e reivindicar seus direitos. A reportagem buscou pôr em prática as técnicas jornalísticas de documentação, estilo, estrutura narrativa, sistema de codificação, diagramação e edição. De fundo, questionar e afirmar o papel do Comunicador na sociedade, enquanto categoria portadora de uma função social e de importância relevante e crucial... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Igualdade; Movimentos sociais; Urbanização; Social movements